2017
DOI: 10.1038/hr.2017.72
|View full text |Cite
|
Sign up to set email alerts
|

EPA:DHA 6:1 prevents angiotensin II-induced hypertension and endothelial dysfunction in rats: role of NADPH oxidase- and COX-derived oxidative stress

Abstract: Eicosapentaenoic acid:docosahexaenoic acid (EPA:DHA) 6:1, an omega-3 polyunsaturated fatty acid formulation, has been shown to induce a sustained formation of endothelial nitric oxide (NO) synthase-derived NO, a major vasoprotective factor. This study examined whether chronic intake of EPA:DHA 6:1 prevents hypertension and endothelial dysfunction induced by angiotensin II (Ang II) in rats. Male Wister rats received orally corn oil or EPA:DHA 6:1 (500 mg kg per day) before chronic infusion of Ang II (0.4 mg kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…We did not observe any synergistic effects of ACE-I and EPA combination in BC cell proliferation and migration, possibly due to their competitive anti-inflammatory in vitro mechanisms of action via EGFR and/or NF-κB (Rel-A) signaling pathways [19,53]. Moreover, many preclinical studies reported antihypertensive and anti-inflammatory roles of n-3 PUFAs respectively via ACE-2 upregulation, Ang II downregulation, and partly via GPCR-mediated NF-κB modulation [22,54,55]. Importantly, to our knowledge, we are the first to report the potential anti-inflammatory roles of ACE-I and EPA combination in targeting adipocyte and BC cell interactions.…”
Section: Discussionmentioning
confidence: 98%
“…We did not observe any synergistic effects of ACE-I and EPA combination in BC cell proliferation and migration, possibly due to their competitive anti-inflammatory in vitro mechanisms of action via EGFR and/or NF-κB (Rel-A) signaling pathways [19,53]. Moreover, many preclinical studies reported antihypertensive and anti-inflammatory roles of n-3 PUFAs respectively via ACE-2 upregulation, Ang II downregulation, and partly via GPCR-mediated NF-κB modulation [22,54,55]. Importantly, to our knowledge, we are the first to report the potential anti-inflammatory roles of ACE-I and EPA combination in targeting adipocyte and BC cell interactions.…”
Section: Discussionmentioning
confidence: 98%
“…We also found that TXA 2 production can be affected by antioxidant therapy and may affect the degree of UAE. The importance of oxidative stress in the pathogenesis of hypertensive organ damage has been extensively studied [16,[26][27][28][29]. The excessive production or decreased metabolism of ROS, such as superoxide anion (O 2 − ), hydrogen peroxide (H 2 O 2 ), and hydroxyl anion (OH − ), can lead to oxidative stress that alters the redox state and causes the redirection of redox-regulated signaling pathways and cellular dysfunction or damage [30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the intake of EPA:DHA 6:1 prevented the development of endothelial dysfunction in the secondary branch of the mesenteric artery in a rat model of hypertension induced by the chronic infusion of angiotensin II both by reducing the endothelium-dependent COX-mediated contractile response and by improving the EDH-and NO-mediated relaxations [24]. Such a beneficial effect of the EPA:DHA 6:1 treatment on the endothelial function was associated with an increased plasma level of omega-3 PUFAs compared to omega-6 PUFAs, and with a reduction of nearly 65% in the omega-6/omega-3 ratio [24]. The reduction of the omega-6/omega-3 ratio has been shown to exert a beneficial effect on the vascular system by improving the activation of eNOS and by reducing the level of oxidative stress and the inflammatory response [19,25,26].…”
Section: Discussionmentioning
confidence: 90%
“…A previously published study showed that a 2-week intake of EPA:DHA 6:1 improved the endothelial function in the mesenteric artery of old rats with established age-related endothelial dysfunction [22]. Similarly, the intake of EPA:DHA 6:1 prevented the development of endothelial dysfunction in the secondary branch of the mesenteric artery in a rat model of hypertension induced by the chronic infusion of angiotensin II both by reducing the endothelium-dependent COX-mediated contractile response and by improving the EDH-and NO-mediated relaxations [24]. Such a beneficial effect of the EPA:DHA 6:1 treatment on the endothelial function was associated with an increased plasma level of omega-3 PUFAs compared to omega-6 PUFAs, and with a reduction of nearly 65% in the omega-6/omega-3 ratio [24].…”
Section: Discussionmentioning
confidence: 94%